Impact of Government Total Health Expenditure on the Economic Determinants for the Demand of Healthcare in Nigeria 1990-2015 - Yusuf, Patience (My University, 2020)
This study examines the relationship between government total health expenditure and the economic determinants for the demand of healthcare in Nigeria, covering the period 1990- 2015. The main source of data utilized is from CBN Statistical Bulletin 2015 and World Development Indicators 2016. By employing the use of the multiple regression model as the main statistical tool of analysis, the study established that there exists a positive relationship between government total health expenditure and the economic determinants for the demand of healthcare in Nigeria except one of the variables which is aged dependency ratio that has a negative relationship with government total health expenditure. Based on the findings, the study recommends that there is need for the inclusion of health care facilities and skilled health personnel in the government health expenditure, to build centres across the country to care for the dependent aged in the society. Also, the enlightenment on health issues needs to be intensified so that the health status of Nigerians is improved and greater attention should be paid to the supply and demand of health inputs in the country. Keywords: health, healthcare, healthcare demand, government healthcare expenditure
Keywords: Government expenditure; Health; Healthcare demand